EFFECT OF IMMERSION FREQUENCY ON SEEDLING PRODUCTION OF PORANG (AMORPHOPHALLUS MUELLERI) CULTIVATED IN A TIS RITA BIOREACTOR - Noor Fauzia, Aura
The porang plant (Amorphophallus muelleri) is an alternative carbohydrate source that has high economic value. Besides being used as a food ingredient, the high glucomannan content in porang tubers plays a role as a prevention of diabetes and cholesterol because it has a high fiber content and low calories. The various benefits of porang plants have resulted in increasing market demand, which requires the propagation of porang plant seeds in tissue culture using the TIS-RITA® bioreactor. Through this method, it can produce porang plant seedlings optimally and in a short time. The purpose of this study was to determine the effect of variations in the frequency of immersion for 2 minutes every 6 or 18 hours with ½ MS medium and 2 ppm BAP hormone for 14 days on growth analysis which includes determination of relative growth rate (RGR), height increase, multiplication rate, total chlorophyll content, survival rate, and determination of medium bioconversion (pH, sucrose, conductivity, and C-organic content, dissolved oxygen, and N content), as well as mass balance analysis of porang plant culture results (Amorphophallus muelleri) using TISRITA® bioreactor. The results showed that porang plant explants for 2 minutes every 6 hours produced a relative growth rate (RGR) value of 40,527 ± 2,51 mg/day with a biomass increase of 74,66%, a height increase value of 0,357 ± 0,08 mm/day, a multiplication rate of 9 ± 0,882 number of shoots/explants, survival rate of 100% for both immersion frequency variations, total chlorophyll content of 38,19 ± 2,802 SPAD, and optimal nutrient consumption characterized by a decrease in pH, sucrose, conductivity, and C-organic content, dissolved oxygen, and N content. The efficiency of sucrose bioconversion into biomass through actual and theoretical mass balance analysis obtained that the frequency of immersion for 2 minutes every 18 hours was higher than that of immersion every 6 hours. Therefore, based on the results of this study, it can be concluded that the use of the TIS-RITA® bioreactor with a soaking frequency of 2 minutes every 6 hours is a good seedling production system for porang plants